Analysis of sequence polymorphism of OsHKT1;5 gene in rice (Oryza sativa L.) - Huy Duong, Nguyen; Xuan An, Tran; Phuc, Do Thi (Vietnam Journal of Biotechnology, 2022)
In salt stress conditions, the excessive accumulation of Na+ ion in the cytoplasm could cause ion toxicity, metabolic imbalances, and reduction in growth of plant. The ability of maintaining a low Na+ concentrations or low Na+/K+ ratio in cytosol plays the important roles of plant adapt to salinity stress. In rice, the HKT transporter family has been proven to be critical for salt tolerance and the maintenance of Na+, K+ homeostasis under salinity conditions. In this study, we conducted the sequence polymorphisms analysis in the OsHKT1;5 coding region in order to detect the potential allelic variants in some local rice cultivars in Viet Nam. The exon 1 region and exon 2-3 region of OsHKT1;5 gene were amplified by PCR in two separate reactions. After direct sequencing of PCR products, the full length coding region of OsHKT1;5 gene was obtained and compared to reference Nipponbare OsHKT1;5 coding sequence. Accordingly, twelve nucleotide substitutions in coding sequence of OsHKT1;5 were identified, including six non-synonymous substitutions (G382A, C418G, G551A, C994G, C1183G, A1630C) and the other six synonymous substitutions (G225A, C1038G, G1152A, G1261A, G1304C, C1608T). Further analysis revealed that six non-synonymous substitutions (G382A, C418G, G551A, C994G, C1183G, A1630C) caused the changes in amino acids (D128N, P140A, R184H, H332D, V395L, and S544R). The single nucleotide polymorphism A1630C leading substitution of S544R was newly found in the Chiem Rong cultivar. In silico analysis of protein structure and post-translational modifications indicated that amino acid substitutions had no influence on protein structure but led to changes in post-translational modifications such as phosphorylation and SUMOylation.